2018
DOI: 10.1016/j.biopsych.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Animal Models of Posttraumatic Stress Disorder: Behavioral and Biological Phenotypes, and Future Challenges in Improving Translation

Abstract: Increasing predictability of animal models of posttraumatic stress disorder (PTSD) has required active collaboration between clinical and preclinical scientists. Modeling PTSD is challenging, as it is a heterogeneous disorder with ≥20 symptoms. Clinical research increasingly utilizes objective biological measures (e.g., imaging, peripheral biomarkers) or nonverbal behaviors and/or physiological responses to complement verbally reported symptoms. This shift toward more-objectively measurable phenotypes enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
150
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(169 citation statements)
references
References 146 publications
(125 reference statements)
3
150
0
2
Order By: Relevance
“…Anxiety and trauma-related disorders are widespread and costly 5 Comer et al, 2011;Kinley et al, 2011;Salas-Wright et al, 2014;Stein et al, 2017;Wittchen, 6 2002), and remain difficult to treat (Colvonen et al, 2017;Costello et al, 2014;Iza et al, 2013;7 Sinnema et al, 2015). Understanding the neural circuits underlying anxiety is important for 8 refining behavioral and pharmacotherapeutic treatments (Berridge, 2018;Deslauriers et al, 2017;9 Fanselow andPennington, 2018, 2017;Graham et al, 2014;LeDoux and Daw, 2018;Nees et al, 10 2015;Pine and LeDoux, 2017;Tye, 2018). Several recent studies have demonstrated changes in 11 the function of the bed nucleus of the stria terminalis (BNST) in individuals with post-traumatic 12 stress disorder (PTSD) and anxiety disorders (Andreescu et al, 2015;Brinkmann et al, 2018;L 13 Brinkmann et al, 2017;Leonie Brinkmann et al, 2017;Buff et al, 2017;Münsterkötter et al, 14 2015;Rabellino et al, 2018;Straube et al, 2007;Yassa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and trauma-related disorders are widespread and costly 5 Comer et al, 2011;Kinley et al, 2011;Salas-Wright et al, 2014;Stein et al, 2017;Wittchen, 6 2002), and remain difficult to treat (Colvonen et al, 2017;Costello et al, 2014;Iza et al, 2013;7 Sinnema et al, 2015). Understanding the neural circuits underlying anxiety is important for 8 refining behavioral and pharmacotherapeutic treatments (Berridge, 2018;Deslauriers et al, 2017;9 Fanselow andPennington, 2018, 2017;Graham et al, 2014;LeDoux and Daw, 2018;Nees et al, 10 2015;Pine and LeDoux, 2017;Tye, 2018). Several recent studies have demonstrated changes in 11 the function of the bed nucleus of the stria terminalis (BNST) in individuals with post-traumatic 12 stress disorder (PTSD) and anxiety disorders (Andreescu et al, 2015;Brinkmann et al, 2018;L 13 Brinkmann et al, 2017;Leonie Brinkmann et al, 2017;Buff et al, 2017;Münsterkötter et al, 14 2015;Rabellino et al, 2018;Straube et al, 2007;Yassa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…RSDS was performed as previously described. 15 In brief, control and RSDS animals were [8][9][10][11][12] week-old wild-type male mice of a C57BL/6J background (Jackson Laboratory #000664, Bar Harbor, ME, USA). Seventy-four total animals were used in this study.…”
Section: Micementioning
confidence: 99%
“…10 In attempts to elucidate the pathophysiology of PTSD, many preclinical rodent models have emerged. 11,12 Repeated social defeat stress (RSDS) is a well-characterized murine model that relies upon the aggressive and territorial nature of retired breeder CD-1 mice, 13 while successfully recapitulating several behavioral and inflammatory aspects of PTSD. 11,12 Furthermore, this model has been reported to produce both susceptible and resilient populations as defined by a single parameter on the social interaction behavioral test (i.e., social interaction ratio <1.0 or ≥1.0, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study investigated how BNST hyperactivation (as recognized in anxiety disorders) modulates fear learning characteristics in a Pavlovian fear conditioning paradigm that is suitable for translational studies by targeting conserved mechanisms (Deslauriers et al, 2018;Flandreau and Toth, 2018). We investigated different phases of fear learning, i.e.…”
Section: Introductionmentioning
confidence: 99%